Helmet Ventilation for Pediatric Patients During the COVID-19 Pandemic: A Narrative Review - Mu, Shu-Chi; Chien, Yu-Hsuan; Lai, Pin-Zhen; Chao, Ke-Yun (Frontiers in Pediatrics, 2022)
The air dispersion of exhaled droplets from patients is currently considered a major route of coronavirus disease 2019 (COVID-19) transmission, the use of noninvasive ventilation (NIV) should be more cautiously employed during the COVID-19 pandemic. Recently, helmet ventilation has been identified as the optimal treatment for acute hypoxia respiratory failure caused by COVID-19 due to its ability to deliver NIV respiratory support with high tolerability, low air leakage, and improved seal integrity. In the present review, we provide an evidence-based overview of the use of helmet ventilation in children with respiratory failure.